2013
DOI: 10.1093/eurheartj/eht307.p589
|View full text |Cite
|
Sign up to set email alerts
|

High glucose-induced increased expression of endothelin-1 in human endothelial cells is mediated by activated CCAAT/enhancer-binding proteins

Abstract: High glucose-induced endothelial dysfunction is partially mediated by the down-stream pathophysiological effects triggered by increased expression of endothelin-1 (ET-1). The molecular control mechanisms of ET-1 synthesis are yet to be discovered. Members of the CCAAT/enhancer-binding proteins (C/EBP) family are important regulators of key metabolic processes, cellular differentiation and proinflammatory genes. In this study, we aimed at elucidating the role of C/EBP in mediating the high glucose effect on ET-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…As previously discussed, ET-1 levels are pathologically elevated in diabetes [10,11]. Research indicates that high glucose (the primary feature of diabetes) can induce ET-1 levels [22]. Hence, it is fitting that our ET-trap construct also has a positive effect on returning ECM protein levels back to basal levels after high glucose treatment ( Figs.…”
Section: Discussionsupporting
confidence: 51%
“…As previously discussed, ET-1 levels are pathologically elevated in diabetes [10,11]. Research indicates that high glucose (the primary feature of diabetes) can induce ET-1 levels [22]. Hence, it is fitting that our ET-trap construct also has a positive effect on returning ECM protein levels back to basal levels after high glucose treatment ( Figs.…”
Section: Discussionsupporting
confidence: 51%
“…Previous researches show that multiple signal pathways, including PI3-K, NF-κB, JNK and p38, contribute to the expression of CEBP/α in different cells. [23][24][25] Furthermore, HBX could induce the activation of these pathways to regulate the expression of various cellular factors in HCC cells. 17,41,42 In addition, JNK and NF-κB pathways have been reported to induce the expression of IL-34 in cells with multiple types.…”
Section: Discussionmentioning
confidence: 99%
“…Current reports showed that CEBP/α expression is mainly mediated by PI3-K, 23 NF-κB, 24 JNK and p38 pathways in different cells. 25 We examined whether HBX was able to promote CEBP/α expression through these pathways. The results showed that HBX could activate PI3-K, NF-κB, JNK and p38 pathways in HCC cells ( Figure 3).…”
Section: Hbx Promotes the Expression Of Cebp/α Via Different Signalmentioning
confidence: 99%
“…In addition, ET-1 regulates PGP expression and transport activity in isolated, intact rat brain capillaries, but not in rat brain capillary endothelial cell lines [11][12][13][14][15]. In addition, ET-1 activates the p38 mitogen-activated protein kinase (p38MAPK) signaling pathway, which is involved in the regulation of PGP and ET-1 expression [16][17][18][19][20][21][22]. Interestingly, ET B receptor activation potentiates the production and secretion of more ET-1 in an autocrine positive feedback loop [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%